Aptamer BAX 499 mediates inhibition of tissue factor pathway inhibitor via interaction with multiple domains of the protein. Issue 6 (3rd July 2013) - Waters, E. K.; Genga, R. M.; Thomson, H. A.; Kurz, J. C.; Schaub, R. G.; Scheiflinger, F.; McGinness, K. E.
Summary Background Tissue factor pathway inhibitor (TFPI) is a multidomain protein that negatively regulates the coagulation cascade. TFPI inhibits the tissue factor (TF)–activated factor VII–activated FX (FXa) complex during TF‐mediated coagulation initiation. The aptamer BAX 499 binds specifically to TFPI and inhibits its function, mediating a procoagulant effect in both in vitro and in vivo models of hemophilia. Objectives This study sought to identify the regions of TFPI that are critical for BAX 499 binding, and to determine how binding mediates aptamer inhibition of TFPI. Methods and Results In vitro biochemical methods were used to evaluate the BAX 499 interaction with and inhibition of TFPI. Binding experiments indicated that the full‐length TFPI protein is required for tight aptamer binding. Binding‐competition experiments implicated the Kunitz 1, Kunitz 3 and C‐terminal domains of TFPI in aptamer binding, a finding that is supported by hydrogen–deuterium exchange experiments, and indicated that aptamer and FXa can bind simultaneously to TFPI. In enzymatic assays, BAX 499 inhibited TFPI in a manner that is distinct from domain‐specific antibodies, and aptamer inhibitory activity is reduced in the presence of the TFPI cofactor protein S. Conclusions These studies demonstrate that BAX 499 binds to TFPI via multiple domains of the protein in a manner that is distinct from other TFPI inhibitors, mediating a mechanism of inhibition that does not involve direct competition with FXa. With this unique inhibitory mechanism, BAX 499 provides a useful tool for studying TFPI biology in health and disease.